2022
DOI: 10.5435/jaaosglobal-d-21-00272
|View full text |Cite
|
Sign up to set email alerts
|

Erector Spinae Plane Blocks With Liposomal Bupivacaine for Pediatric Scoliosis Surgery

Abstract: Pain management in patients with adolescent idiopathic scoliosis (AIS) undergoing posterior spinal fusion can be challenging. Various analgesic techniques are currently used, including enhanced recovery after surgery principles, spinal opioids or continuous epidural infusion, intravenous methadone, or surgical site infiltration of local anesthetic. Another recently developed technique, ultrasound-guided erector spinae plane blockade (ESPB), has been used successfully in spine surgery and may offer advantages b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 27 publications
0
6
2
Order By: Relevance
“…We also demonstrated that LB was associated with 0.3 days shorter LOS. In a recent case report of 2 AIS patients undergoing PSF, Stondell et al demonstrated decreased opioid use and shorter LOS with the use of a preoperative ESB with LB prior to skin incision 19 . Contrary to our findings, they reported higher pain scores.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We also demonstrated that LB was associated with 0.3 days shorter LOS. In a recent case report of 2 AIS patients undergoing PSF, Stondell et al demonstrated decreased opioid use and shorter LOS with the use of a preoperative ESB with LB prior to skin incision 19 . Contrary to our findings, they reported higher pain scores.…”
Section: Discussioncontrasting
confidence: 99%
“…In a recent case report of 2 AIS patients undergoing PSF, Stondell et al demonstrated decreased opioid use and shorter LOS with the use of a preoperative ESB with LB prior to skin incision. 19 Contrary to our findings, they reported higher pain scores. Similarly, Ballock et al found that among 10,189 pediatric patients who underwent spine surgery, those who received LB had significantly lower in-hospital postoperative opioid consumption and decreased hospital LOS.…”
Section: Discussioncontrasting
confidence: 99%
“…Liposomal bupivacaine has been shown to provide postsurgical analgesia with a similar safety profile to bupivacaine HCl in a variety of surgical scenarios, such as hemorrhoidectomy, total knee arthroplasty, mammoplasty, and thoracic surgery (18,(35)(36)(37). Liposome bupivacaine appears safe when used in fascial plane blocks and peripheral nerve blocks, such as ESPB, paravertebral block, and intercostal nerve block (16)(17)(18)(19)(20)23).…”
Section: Discussionmentioning
confidence: 99%
“…In 2011, liposomal bupivacaine was approved by the U.S. Food and Drug Administration to be used in single-dose wound infiltration for postsurgical analgesia in adults, and then the indication was expanded to transverse abdominis plane blocks and interscalene brachial plexus blocks (14,15). Liposome bupivacaine appears safe when used in fascial plane blocks and peripheral nerve blocks (16)(17)(18)(19)(20). Whether LB is superior to traditional local anesthetics in postoperative analgesia after thoracic surgery remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…In pediatrics, published protocols for idiopathic spinal fusion surgery, a procedure with high incidence of CPSP, are highly variable in their use of opioids, regional anesthesia, and adjuvant analgesic medications including gabapentinoids, muscle relaxants, ketamine, subcutaneous local anesthetic infusions, and dexmedetomidine. [89][90][91][92][93][94][95][96] At this time, there is little evidence to support the use of one perioperative analgesic protocol over another for acute pain in pediatric patients undergoing major musculoskeletal surgery, and no evidence to support any specific pharmacologic approach to prevent the transition to CPSP. Thus, we propose that operative protocols and institutional "best practice" should incorporate universal screening of each child or adolescent undergoing surgery to determine their risk level for developing CPSP.…”
Section: Dovepressmentioning
confidence: 99%